Effectiveness of Dialectical Behavior Therapy on Distress Tolerance and Difficulties in Emotion Regulation among Adolescents with Impulsive Behaviors - Hosseini , Seyed Emad; Ahangar , Motahareh; Sadigh, Marzieh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study was conducted to determine the effectiveness of dialectical behavior therapy on distress tolerance and difficulties in emotion regulation among adolescents with impulsive behaviors. Materials and Methods: This was a quasi-experimental study with a pretest–posttest design and a two-month follow-up period including a control group. The statistical population consisted of adolescents aged 13 to 18 years with impulsive behaviors in Tehran in 2026. A total of 30 eligible adolescents were selected through purposive sampling and were randomly assigned to either the experimental group or the control group, with 15 participants in each group. The experimental group received dialectical behavior therapy skills training based on Linehan’s treatment package during eight 90-minute sessions, whereas the control group received no intervention during this period. Data were collected using the Distress Tolerance Scale developed by Simons and Gaher and the Difficulties in Emotion Regulation Scale developed by Gratz and Roemer. Data were analyzed using the independent samples t-test, Fisher’s exact test, and two-way repeated measures analysis of variance in SPSS version 26. Findings: The results indicated that there were no significant differences between the experimental and control groups in terms of demographic characteristics. Furthermore, the results of the two-way repeated measures analysis of variance demonstrated that the interaction effect of group and time on distress tolerance and difficulties in emotion regulation was significant. Mean comparisons showed that distress tolerance scores in the experimental group increased from the pretest to the posttest stage, whereas difficulties in emotion regulation scores decreased. These changes remained largely stable at the two-month follow-up stage, while no considerable changes were observed in the control group. Conclusion: Based on the findings of the study, dialectical behavior therapy can increase distress tolerance and reduce difficulties in emotion regulation among adolescents with impulsive behaviors. Therefore, the application of this approach in schools, counseling centers, and adolescent clinics may be beneficial for improving emotional skills, enhancing the ability to tolerate difficult situations, and reducing impulsive reactions.